About Almaty kazakh language corpus (Eurasian Journal of Philology Science and Education, 2016)
Modern information technologies and technical means open new opportunities for linguistic research on the basis of language corpora. The description of the pilot version of Almaty Corpus of the Kazakh Language (ACKL), as a component of the National Corpus of the Kazakh Language (NCKL) representing the reference system on the basis of extensive fund of the marked texts of the literary Kazakh language created within the State program of functioning and development of languages (2011-2020) is presented in the article. The history of creation, role, fullness, markedness and expediency of using ACKL in linguistic researches, in practice of teaching the Kazakh language, as a native and foreign one, as a source for drawing up lexicographic editions is described.
Keywords: language corpus; national corpus; reference system; subcorpus; marking of texts; applied value of the corpus.